A systematic method towards generating the Malaysian folktale classification system - Harun, Harryizman; Jamaludin, Zulikha (2014)
This paper explicates two methods used in a study conducted to propose a Malaysian folktale classification system.Fundamentally, three substantial folktale classification systems exist and individually, each system classifies based on three distinctive folktale units: type, motif, and function. Independently, type and motif classify based on the content of folktale while function, the structure of folktale.The study aims to generate the Malaysian folktale classification system based on an amalgamation of the three renowned units of folktale.To classify, the method selected is structural-semantic analysis which encompassed three levels of classification. It classifies sequentially according to the content and structure of the Malaysian folktale. Nonetheless, prior to classify, an identification of the Malaysian folktales must take place Such task is steered by two qualifying factors: formal features in an operational definition developed in the study and also an ownership of the folktales. These factors function as a filter towards safeguarding the study from contamination of forms of folklore other than the study intends to examine.Additionally, they assist in discriminating between modern folktales and the ones with embedded cultural values of different generations. In a nutshell, this paper reveals the methods to identify and classify the Malaysian folktales.